DECREASING NAUSEA AND VOMITING DUE TO CHEMOTHERAPY INDUCTION THROUGH PEPPERMINT AROMATHERAPY - indah - lestari (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
Nausea and vomiting often appear with under various conditions, includ being a common side effect of using anti-neoplastic drugs. Chemotherapy-induced nausea and vomiting (CINV) is a major problem that can often alter the quality of life (QoL) and patient adherence to treatment if left untreated. Aromatherapy peppermint is one form of improvised non pharmacological handling of CINV. This study aims to determine the effectiveness of giving peppermint aromatherapy in reducing CINV in chemotherapy patients.This study was a quasy experiment with a Non Equivalent with Control Group design, with total sample groups of 285 respondents with consecutive technique. Parameters in this study used Rhodes Index Nausea Vomiting and Reching (RINVR). The data were analyzed using Wilcoxon sign rank test as a test of change of nausea scale of pre and post vomiting in experimental group using peppermint aromatherapy and control group. The results of the differences from both groups were tested with mann whitney-u test. Wilcoxon sign rank test analysis, showing differences in the incidence of nausea and vomiting in the control group and intervention group. The result of change of decrease in experimental group value Ï = 0,001 is more significant than control group with value Ï = 0,020. The difference is tested with mann whitney-u test with the result value Ï = 0.002. Aromatherapy works in oneâ€™s body by triggering the release of neurotransmitter like enkephalin and endorphin which have analgesic effect and increase the feeling of comfortable and relax. Through inhalation, the fragrance of aromatherapy is transmitted through two ways, first is through limbic system into hypothalamus until pituitary. Second is transmitted through olfactory cortex, into thalamus and then head to neocortex. Through these two ways aromatherapy shall be processed until it creates individual perception Keywords : CINV, Chemotherapy, Peppermint aromatherapy